Effect of botulinum toxin-A injection on intraocular pressure and proptosis in thyroid associated orbitopathy - Lešin, Mladen (Array, 2009)
Abstract: The aim of this study was to evaluate the effects of extraocular muscle injection of botulinum toxin-A (BTX-A) on intraocular pressure (IOP) and proptosis in patients with ocular motility disturbances in thyroid associated orbitopathy (TAO). In 17 patients (20 eyes) with restrictive strabismus and diplopia, BTX -A injections were applied. Intraocular pressure was measured with a Goldmann applanation tonometer in primary gaze position before and 2–4 weeks after BTX-A injection. Extraorbital prominention of the eyeball was measured before and after BTX -A injection using a Hertel instrument. Before the injection, the mean IOP in primary position of gaze was 18.6± 2.8 mmHg and 2–4 weeks after BTX-A injection was 16.9±3.3 mmH; (p=0.001). There was no statistically significant difference in Hertel egzophthalmometer readings before and after BTX-A injection, 21.5±2.7 mm vs 22.0± 2.6 mm; (p=0.678). In conclusion, BTX-A injection has a secondary lowering effect on IOP in TAO due to relaxation of extraocular muscles, but with no influence on proptosis